The impact of organisational resilience on construction project success: evidence from large-scale construction in China - Yang, Jie; Cheng, Qian (Journal of Civil Engineering and Management, 2020)
Environmental uncertainty, social public events and increasing challenges has raised the urgency for the need to improve organisational resilience of construction projects, which is of great significance to the success and governance of construction projects. This study explores the organisational resilience factors that affect the success of construction projects based on a literature review and the actual situation and abstracts them into four explanatory variables: situation monitoring, organisational structure, organisational culture and participants. Through the crisp-set Qualitative Comparative Analysis (csQCA) method, 15 Chinese cases that meet the research conditions are compared and analysed, and two effective conditional configurations obtained. The results show that in the absence of timely monitoring of the changes in the situation, flexible organisational structure, cohesive organisational culture and participation of multiple subjects can promote the success of the construction project. The synergy of multiple participants can make up for the lack of organisational culture to a certain extent. Moreover, public participation and big data applications should be given full attention in the improvement of organisational resilience. This study can provide a basis for construction projects to reasonably match organisational resilience conditions to cope with crisis and challenges.